C-amidation of substituted β3 oligoamides yields novel supramolecular assembly motif. (22nd October 2021) - Buchanan, Claire; Puskar, Ljiljana; Garvey, Christopher J; Mechler, Adam
Abstract: N-acylated substituted β 3 oligoamides are known to form unique supramolecular nanorods based on a 3-point hydrogen bond self-assembly motif. This motif is an intermolecular extension of the hydrogen bonding network that stabilizes the 14-helix secondary structure unique to β 3 oligoamides. Acetylation of the N-terminus of the molecule provides the necessary third hydrogen bond pair of the motif. Here, the possibility of introducing the third hydrogen bond pair via amidation of the C terminus is investigated. While similar in purpose, this modification introduces a chemically distinct new self-assembly motif, also removing the bulky carboxyl group that does not fold into the 14 helix positioning instead as a side chain. Three substituted β 3 oligoamide variants with the base sequence LIA (where the letters denote β 3 residues with side chains analogous to α amino acids) were compared: N-acylated Ac- β 3 [LIA] as a reference, C-amidated β 3 [LIA]-CONH2, and β 3 [LIA] with free unmodified N and C termini as a negative control. The three variants were dissolved in water to promote self-assembly. The self-assembly was characterised using mid- and far-infrared spectroscopy, small angle x-ray scattering (SAXS) and atomic force microscopy (AFM). IR measurements confirmed that all three samples were in a similar conformation, consistent with pseudo 14-helical secondary structures. Far-infrared spectroscopy measurements of β 3 [LIA]-CONH2 showed distinct peaks consistent with highly organised skeletal modes, i.e. regular supramolecular assembly, that was largely absent from the other two oligoamides. Modelling of SAXS data is consistent with elliptical cylinder structures resulting from nanorod bundling for both β 3 [LIA]-CONH2 and Ac- β 3 [LIA], but not in the unmodified sample. Consistently, AFM imaging showed large nanorod bundling structures in β 3 [LIA]-CONH2, varied bundling structures in Ac- β 3 [LIA], and only aggregation in β 3 [LIA]. Amidation showed much more organised and robust assembly compared to acetylation, providing a new, easy to synthesize self-assembly motif for helical nanorod assembly that is similar but distinct to N-acylation